Analyzing The Role Of The PDCA Method In Supporting Continuous Improvement: A Case Study Of A Coal Mining Contractor In South Kalimantan - Regiano Al-Alif; Anjar Priyono (Journal of Collaborative Industrial Management (JCIM), 2026)
The mining industry operates in a high-risk environment in which transportation activities contribute significantly to occupational accidents and operational losses. In Indonesia, transportation-related incidents in mining operations remain a critical safety issue, highlighting the need for systematic and sustainable improvement approaches. This study aims to analyze the implementation of the Plan–Do–Check–Act (PDCA) method as a continuous improvement framework in reducing transportation-related incidents within a coal mining contractor operating in South Kalimantan. This study employs a qualitative case study approach. Data were collected through direct field observations conducted during an industrial internship, semi-structured interviews with key personnel involved in the improvement program, and analysis of internal company documents related to safety performance and continuous improvement initiatives. The PDCA framework was used as the primary analytical lens to examine improvement activities across the planning, implementation, evaluation, and standardization stages. The findings indicate that the PDCA method was effectively implemented to identify dominant transportation safety risk factors, particularly unsafe driving behavior and limitations in manual monitoring systems. Improvement actions implemented during the Do stage included the adoption of digital fit-for-duty systems, enhanced transportation monitoring technologies, and strengthened supervisory coaching. The Check stage demonstrated measurable improvements in safety compliance and reductions in unsafe driving behavior, while the Act stage focused on standardizing successful practices to support sustainability. This study concludes that the PDCA method functions as an effective continuous improvement tool for strengthening transportation safety management in high-risk mining operations. The findings provide practical insights for mining contractors seeking to enhance safety performance through structured, data-driven, and sustainable improvement cycles.